Reevaluating factors in global Universal Health Coverage implementation pre-COVID-19 - Rahayu Lubis; Fauzi Budi Satria; Santi Martini; Harnavi Harun; Rafdzah Ahmad Zaki; Surya Utama; Juanita (Elsevier, 2024)
Background: Universal Health Coverage (UHC) strives to ensure equitable access to high-quality healthcare services for all. Despite this goal, the COVID-19 pandemic exposed significant healthcare shortages worldwide. This study reevaluates key determinants of UHC implementation on a global scale before the pandemic, offering insights to shape strategies for achieving UHC by 2030 in light of current circumstances. Methods: This ecological study analyzed data from 178 countries. UHC implementation was assessed using two indicators: Health Service Coverage (HSC) and Financial Protection (FP). Independent variables, including the Human Development Index (HDI), Health Worker Density (HWD), and Governance Effectiveness (GE), were proposed based on the Systemic Rapid Assessment Toolkit (SYSRA) framework. Data from 2000 to 2019 were sourced from open databases. Statistical analysis was performed using R version 4.3.1, with a significance level of p < 0.05. Results: Countries with higher HDI exhibited significantly better HSC (p < 0.05) and FP (p < 0.05). Furthermore, HDI emerged as the primary contributor to HSC (accuracy = 0.77, Kappa = 0.64), while HSC played a central role in determining FP (accuracy = 0.61, Kappa = 0.21). Governance Effectiveness (GE) also significantly influenced FP in addition to HSC. Conclusion: Rather than solely focusing on building healthcare infrastructure and expanding the healthcare workforce, balancing progress in both development and governance is a promising approach for countries striving to attain UHC by 2030.